Standardized protocols for blood collection and analysis in elasmobranchs: a practical guide for clinicians and researchers - David, Hugo; García-Párraga, Daniel; Pereira, Nuno; Morón-Elorza, Pablo (Frontiers in Veterinary Science, 2026)
Blood analysis represents a crucial, yet often underutilized, diagnostic tool in elasmobranch medicine. Its broader application has been limited by the absence of standardized protocols and consistent species-specific reference values. The variability in sampling techniques, analytical methods, and data interpretation presents significant challenges for both clinical practices and cross-institutional research. This manuscript offers a comprehensive, evidence-based guideline for blood collection and analysis in elasmobranchs. It details best practices for documenting biological and procedural metadata to enhance sample comparability and provides practical recommendations for venipuncture site selection, blood gas analysis, hematology, biochemistry, and plasma protein electrophoresis. The techniques described are optimized for use with materials and equipment commonly found in veterinary settings. The adoption of these standardized protocols is expected to improve diagnostic accuracy, facilitate the development of reliable species-specific reference ranges, and enable the integration of health data across facilities. Routine implementation in monitored populations is encouraged to set reliable reference physiological levels, support early disease detection and advance veterinary care, as well as contribute to the broader field of elasmobranch health, research and conservation.